2011
DOI: 10.1167/iovs.10-5964
|View full text |Cite
|
Sign up to set email alerts
|

Subfoveal Choroidal Blood Flow and Central Retinal Function in Retinitis Pigmentosa

Abstract: These data indicate significant alterations of subfoveal choroidal hemodynamic in RP and suggest a link between the alteration of ChBF and the RP-associated central cone-mediated dysfunction as assessed by the FERG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
71
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 21 publications
10
71
0
2
Order By: Relevance
“…Choroidal blood flow studies in RP patients6 and fluorescein angiography studies in RP patients,13–15 further support our findings that choroidal circulation and volume are reduced in RP. Falsini and associates6 demonstrated that RP patients with preserved vision have reduced subfoveal choroidal blood flow, and that there appears to be an association between choroidal blood flow and retinal function as measured by focal macular electroretinograms, further implicating the role of choroidal circulation in the pathogenesis of RP.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Choroidal blood flow studies in RP patients6 and fluorescein angiography studies in RP patients,13–15 further support our findings that choroidal circulation and volume are reduced in RP. Falsini and associates6 demonstrated that RP patients with preserved vision have reduced subfoveal choroidal blood flow, and that there appears to be an association between choroidal blood flow and retinal function as measured by focal macular electroretinograms, further implicating the role of choroidal circulation in the pathogenesis of RP.…”
Section: Discussionsupporting
confidence: 75%
“…The known genes encode phototransduction cascade proteins, retinol metabolism and cell–cell interaction proteins, photoreceptor structural proteins and transcription factors among other proteins 6. While many of these genes only cause a small proportion of RP cases, several account for a relatively larger proportion.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, both retinal and choroidal blood flow have previously been shown to be reduced in patients with RP, by using color Doppler imaging and laser Doppler flowmetry [2–4, 35, 36], and fluorescein angiography studies further support that choroidal circulation and volume are reduced and disturbed in RP [3739]. …”
Section: Discussionmentioning
confidence: 97%
“…Several studies have reported altered choroid circulation in patients with RP (Falsini et al. 2011). However, there is a lack of agreement on the findings of flow area in the choriocapillaris between two previous studies: while Parodi et al.…”
Section: Discussionmentioning
confidence: 99%